Chaotic Flows Correlation effects and coherent structures - Bakunin, Oleg G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The book introduces readers to and summarizes the current ideas and theories about the basic mechanisms for transport in chaotic flows. Typically no single paradigmatic approach exists as this topic is relevant for fields as diverse as plasma physics, geophysical flows and various branches of engineering. Accordingly, the dispersion of matter in chaotic or turbulent flows is analyzed from different perspectives. Partly based on lecture courses given by the author, this book addresses both graduate students and researchers in search of a high-level but approachable and broad introduction to the topic.
Part I Diffusion and Correlations -- Introduction -- Advection and Transport. the Langevin Equation and Transport -- Part II Lagrangian Description -- Lagrangian Description of Chaotic Flows -- Lagrangian Chaos -- Part III Phenomenological Models -- Correlation Effects and Transport Equations -- the Taylor Shear Dispersion -- Part IV Fractals and Anomalous Transport -- Fractal Objects and Scaling -- Random Shear Flows and Correlations -- Part V Structures and Nonlocal Effects -- Transport and Complex Structures -- Fractional Models of Anomalous Transport -- Part VI Isotropic Turbulence and Scaling -- Isotropic Turbulence and Spectra -- Turbulence and Scalar -- Relative Diffusion and Scaling -- Two Dimensional Turbulence and Transport -- Part VII Convection and Scaling -- Convection and the Rayleigh Number -- Convection and Turbulence -- Part VIII Structures and Complex Flow Topology -- Coherent Structures and Transport -- Flow Topology Reconstruction and Transport -- References -- Index.
Keywords: Physics; Physical geography; Physics; Statistical Physics, Dynamical Systems and Complexity; Classical Continuum Physics; Geophysics/Geodesy.; Fluid- and Aerodynamics